REPRESENTASI TOXIC MASCULINITY & BULLYING PADA IKLAN LAYANAN MASYARAKAT KEMENDIKBUD RI “INI GAK LUCU” - Krisna Anjasmani, Rury; Widyananda Putra, Ricky (Kartala, 2025)
In 2023, toxic masculinity and bullying will become a hot topic of conversation among Indonesian and foreign people. There are many things that influence toxic masculinity and bullying, from the way you dress, speaking style, accessories are a form of communication. Through clothing, a person can convey messages to others. This message is used for imaging or a form of branding of a person himself. Based on this, the author is interested in examining the visual representation conveyed in the public service advertisement (ILM) entitled "This Isn't Funny" regarding toxic masculinity and bullying. This research uses Charles Sanders Peirce's semiotic analysis to translate the meaning of symbols in public service advertisements (PSAs). In Peirce's semiotics it is divided into three main elements, namely signs, objects and interpretants. The method used is qualitative. Aims to explain phenomena in depth, through in-depth data collection. The result that can be taken from this research is that the moral message conveyed through the visual public service advertisement entitled "This Isn't Funny" can open our eyes to appreciate each other more regardless of gender.